2013
DOI: 10.1093/toxsci/kft010
|View full text |Cite
|
Sign up to set email alerts
|

Propiconazole Inhibits Steroidogenesis and Reproduction in the Fathead Minnow (Pimephales promelas)

Abstract: Conazoles are designed to inhibit cytochrome P450 (CYP) 14α-demethylase, an enzyme key to fungal cell wall formation. In vertebrates, conazoles may inhibit other CYPs, potentially disrupting processes like sex steroid synthesis. Propiconazole is a current-use pesticide that is among the first chemicals being tested in the U.S. Environmental Protection Agency endocrine disruptor screening program. Fathead minnows (Pimephales promelas) were exposed to 0, 5, 50, 500, or 1000 µg propiconazole/l in a 21-day study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 45 publications
(90 reference statements)
4
51
1
Order By: Relevance
“…CYP51 catalyse the demethylation of lanosterol in the cholesterogenic process which is also the target of triazole compounds. Previous research documented that cholesterol level in plasma decrease associated with inhibition of hepatic expression of CYP51 and HMGCR in propiconazole treated fathead minnow (Skolness et al, 2013). In this work, similar with the results of Skolness et al (2013), the reduction of gene expression of CYP51 and HMGCRa, were observed with the decreased TCHO level in male zebrafish liver.…”
Section: Discussionsupporting
confidence: 88%
“…CYP51 catalyse the demethylation of lanosterol in the cholesterogenic process which is also the target of triazole compounds. Previous research documented that cholesterol level in plasma decrease associated with inhibition of hepatic expression of CYP51 and HMGCR in propiconazole treated fathead minnow (Skolness et al, 2013). In this work, similar with the results of Skolness et al (2013), the reduction of gene expression of CYP51 and HMGCRa, were observed with the decreased TCHO level in male zebrafish liver.…”
Section: Discussionsupporting
confidence: 88%
“…Both these two genes play important parts in cholesterol synthesis. Previous research has shown that a decrease in the cholesterol level in plasma occurred with the down-regulation of hepatic CYP51 and HMGCR in fathead minnow (P. promelas) treated with propiconazole (Skolness et al, 2013). Therefore difenoconazole may also cause a decrease in the level of total cholesterol because its mode of action and gene expression effects are similar to propiconazole.…”
Section: Discussionmentioning
confidence: 98%
“…Morrison et al (2014) found that ketoconazole has the potential to inhibit zebrafish CYP51, based on the results of a docking experiment. Skolness et al (2013) demonstrated that propiconazole could inhibit steroidogenesis in the fathead minnow (Pimephales promelas) and down-regulated the expression of some key genes, such as CYP51, HMGCR and FDPS, in the hepatic synthesis process. In the present study, a significant decrease in the hepatic expression of cyp51, hmgcra, and fas was observed in the groups exposed to a high difenoconazole concentration, which is in good agreement with previously reported results.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 1 benefit of including this type of table in reports is that it may compel authors to more methodically analyze their histologic specimens and data interpretations prior to publication. As a positive example, Table 8 is a reprint from 1 of the reviewed manuscripts [13] of a simple data table that elegantly portrays the histopathologic prevalence and severity results. In terms of data credibility, a third example of a weakness was dependence on transmission electron microscopy (TEM) data as the sole or primary means of identifying morphologic effects of chemical exposure.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…a From Skolness et al [13]; reprinted by permission. were published 11 to 15 yr ago (62%; n ¼ 47); in contrast, the lowest percentages involved articles that were published either within the past 5 yr (50%; n ¼ 54) or more than 15 yr ago (50%; n ¼ 16).…”
Section: Histopathology Credibility Scoresmentioning
confidence: 99%